Islamic populism: a non-Western response to globalisation - Alberto Priego (Revista CIDOB d'Afers Internacionals, 2018)
Globalisation’s excesses, the Muslim world’s hybrid regimes and the lack of credibility of pan-Arab and pan-Islamic projects have, along with other factors, caused a significant part of the umma to seek alternative responses to the traditional political options. As well as neo-fundamentalist, post-Islamist and conservative responses, in some Islamic societies other options such as “Islamic populism” are beginning to emerge, which takes up certain features of the Iranian Revolution but incorporating new demands deriving from contemporary political, social and economic conditions. This paper seeks to identify the elements that constitute Islamic populism through a comparative study of the cases of Egypt, Turkey, Indonesia and Iran.